Utilization of Social Media as Marketing Dawet Ireng in Kayen District - Muadzimah, Zumrotul (Jurnal Penelitian Ilmu-Ilmu Sosial, 2022)
Kayen is one of the sub-districts in Pati Regency, Central Java, which is located in South Pati. One of the local specialty drinks in the Kayen District is Dawet Ireng. The presence of modern culinary shifts regional specialties such as dawet ireng. The problem in marketing dawet ireng in Kayen District is still using conventional marketing yet not maximizing and using existing digital marketing such as Instagram, ShoopieFood, GoFood and others. The writing method uses qualitative research methods, data collection can be obtained from the results of interviews, observations, documentation, and combinations or trigulation. Data analysis techniques were carried out using data analysis techniques proposed by Miles and Huberman which included data reduction (data reduction), data presentation (data display), and conclusions or verification (conclusion drawing). Based on the research results, the seller of dawet ireng has not fully used social media as a marketing medium in sales. Still using the conventional way by waiting for buyers to come, there is no training on entrepreneurship training, so they are still not familiar with selling at ShopeeFood and GoFood.